Who Should Pay? : Higher Education, Responsibility, and the Public - Quadlin, Natasha Michaela; Powell, Brian, 1954- (Book collections on Project MUSE., 2021)
"This book examines how Americans think about financial responsibility for college and the implications that public opinion has for higher education access. Specifically, does the public tend to believe that students, parents, or the government should be responsible for the funding of college? Results come primarily from the Constructing the Family and Higher Education interview surveys of 2010 and 2015"--